Peningkatan Literasi Keuangan Keluarga Melalui Penggunaan Aplikasi Keuangan Digital - Umi Hayati; Willy Prihartono; Andre Setiawan; Arief Ilham Syahputra (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Improving family financial literacy is an important aspect of sustainable and healthy financial management. Technological advances have enabled the use of digital financial applications as a tool in improving families' understanding and skills in managing finances. This study aims to analyze the effectiveness of digital financial application education in improving family financial literacy. The research method used involves a qualitative approach with interview and observation techniques for families who use digital financial applications. The results showed that education on the use of digital financial applications contributed to increasing awareness of the importance of more systematic financial management. In addition, the use of digital financial applications helps in financial recording, budget planning, and controlling household expenses. Challenges faced in implementing digital financial applications include limited access to technology, lack of understanding of application features, and resistance to change in financial management habits. Thus, a more comprehensive education strategy and continuous assistance are needed to ensure the successful use of digital financial applications in improving family financial literacy. Translated with DeepL.com (free version).